Maine's Economic Forecast: Modest Growth Ahead - LaChance, Laurie (Maine Policy Review, 1993)
The Maine State Planning Office is preparing to release its most recent long range economic forecast for Maine, which includes projections of employment and output for Maine’s 52 industries through the year 2005 and statewide population projections through the period. The report identifies important market, technical, social, political and demographic forces and quantifies the combined effects of those forces on individual industries. The long range forecast is a planning tool that can be used to plan for and adapt to coming changes or, more proactively, to alert society to potentially undesirable trends that business leaders and policymakers may want to address.
Keywords: Maine economy